2020
DOI: 10.1371/journal.pone.0228196
|View full text |Cite
|
Sign up to set email alerts
|

A systematic scoping review of clinical indications for induction of labour

Abstract: Background The proportion of women undergoing induction of labour (IOL) has risen in recent decades, with significant variation within countries and between hospitals. The aim of this study was to review research supporting indications for IOL and determine which indications are supported by evidence and where knowledge gaps exist. Methods A systematic scoping review of quantitative studies of common indications for IOL. For each indication, we included systematic reviews/meta-analyses, randomised controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
3
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 188 publications
(255 reference statements)
1
60
3
8
Order By: Relevance
“…450)". 19 However, studies compared outcomes from induction at 41 weeks gestation and expectant management until 42 weeks gestation and found not only an increased risk of interventions but a higher cesarean delivery rate in the group that underwent induction at 41 weeks. 20,21 Cochrane review concluded that policy of labor induction compared with expectant management is associated with fewer perinatal deaths and cesarean sections.…”
Section: Discussionmentioning
confidence: 99%
“…450)". 19 However, studies compared outcomes from induction at 41 weeks gestation and expectant management until 42 weeks gestation and found not only an increased risk of interventions but a higher cesarean delivery rate in the group that underwent induction at 41 weeks. 20,21 Cochrane review concluded that policy of labor induction compared with expectant management is associated with fewer perinatal deaths and cesarean sections.…”
Section: Discussionmentioning
confidence: 99%
“…This study found variation in IOL practices, with only 28.7% of units inducing labour for breech presentation, 70.2% for a previous caesarean, 45.7% for suspected fetal macrosomia without diabetes and 63.8% for fetal growth restriction. Inter-hospital variation in indications for IOL is not surprising given the considerable uncertainty in the literature and clinical guidelines around what constitutes best-practice [ 17 , 18 , 40 ]. Variation may relate to uncertainty and confusion in the literature about when to recommend IOL and the consequences of IOL at that specific gestation for the particular indication of IOL [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inter-hospital variation in indications for IOL is not surprising given the considerable uncertainty in the literature and clinical guidelines around what constitutes best-practice [ 17 , 18 , 40 ]. Variation may relate to uncertainty and confusion in the literature about when to recommend IOL and the consequences of IOL at that specific gestation for the particular indication of IOL [ 40 ]. While it was traditionally thought that IOL increased the risk of CS, recent evidence suggests otherwise [ 41 ], and there remains considerable debate around the circumstances in which IOL should be offered.…”
Section: Discussionmentioning
confidence: 99%
“…The primary indicator of the chances of success is the state of the cervix. A cervix that is not ripe increases the likelihood of a non-vaginal delivery [6]. Given that there is an increased progression in perinatal mortality and fetal compromise with gestation extending over 37 weeks, it is during weeks 37 and 41 that induction of labor has the massive potential to better neonatal outcomes [7].…”
Section: Introductionmentioning
confidence: 99%